Impact of Exclusive Breast Feeding on the Growth of Sudanese Children (0-24 Months) - Onsa, Zeinab Osman; Ahmed, Nur Mohammed Khair (Pakistan Journal of Nutrition, 2014)
This study was conducted to prove that exclusive breast feeding is the best way through which infants get their optimum nourishment, thus ensure growth and development. The general objective of this study is to investigate the growth of exclusively breast-fed (EBFD) children (0-24 months). The specific objectives aim to identify the prevalence rate of EBF, its influence on incidence of diarrhea and chest infection was also investigated. The methodology followed was descriptive analytical procedure and information was collected by a questionnaire and anthropometric measurements of infants recorded during the study period. EPI-INFO version 6.2.3. and SPSS programs version 13 were used for data analysis. Three hundred and sixty full term normal weight infants delivered at Omdurman Maternity Hospitalwere included in the study. The result showed that among the mothers 94% were aged 20-39 years, 70% had university education and 69% were housewives. Average family size was 4.1 and 2.5% lived below the UN poverty line. Breast-feeding was initiated by 92.8% of the mothers immediately after birth; its duration was 70.2% for 19-24 month. A new pregnancy was the major reason for stopping breast-feeding. Forty percent of the children were EBFD and they had better duration of breast-feeding at 19-24 months than the non-EBFD (p<0.00). They had lower incidence of diarrhea and chest infections (p<0.00) and lower episodes (p<0.00). Their growth was better in term of weight for age and weight for length (p<0.00).